Types and rates of occupational accidents in nursing students at nursing and midwifery colleges in Tehran - Aghajanloo, A; Niroomand- Zandi, K; Safavi- Bayat, Z; Alavi Majd, H (Advances in Nursing & Midwifery, 2007)
Abstract Background: Today, humans are at increased risk of occupational accidents. Healthcare workers and students expose to many occupational hazards and accidents. Lack of experience and technical expertise places students at more risk. Purpose: This descriptive study was conducted to determine types, rates and causes of occupational accidents in nursing students at Nursing and Midwifery Colleges in Tehran. Methods: 180 nursing students were selected by stratified sampling method. Data were collected with a questionnaire validated and made reliable by content and test-retest methods respectively. Results: 31.3% of the students experienced needle stick, 41.7% sharp injury, 84.8% blood and body fluid exposure, 46.7% exposure to chemotherapy agents, and 33.3% injury and bruise in the past 12 months. There were significant differences in the year of education. Medical, surgical, emergency and oncology wards were identified as risky. Application of protective devices was not satisfactory. Conclusion: According to high rates of some accidents, appropriate educational programs regarding occupational accidents, prevention and timely reporting is necessary. Key words: Occupational accidents, Nursing students.